2016
DOI: 10.5301/jva.5000627
|View full text |Cite
|
Sign up to set email alerts
|

Utility of blind percutaneous jugular venous cannulation in resource-limited settings

Abstract: Our findings suggest that blind percutaneous puncture of the internal jugular vein by trained hands is a relatively safe and effective approach for establishing vascular access for hemodialysis in resource-limited settings. Nevertheless, wherever vascular ultrasound is available, it should be primarily utilized because of the documented advantages of image-guided insertion. Keeping in view the risk of serious peri-procedural complications which include death, the emphasis on image-guided insertion, is appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Multiple studies have evaluated the barriers to usage of US guidance in North America [ 1 , 3 , 4 ]. While ultrasound use for internal jugular CVC placement has become standard of care in both North America and the United Kingdom since approximately 2002, most developing world countries have not adopted this same standard of care and have been slow to adopt its use [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have evaluated the barriers to usage of US guidance in North America [ 1 , 3 , 4 ]. While ultrasound use for internal jugular CVC placement has become standard of care in both North America and the United Kingdom since approximately 2002, most developing world countries have not adopted this same standard of care and have been slow to adopt its use [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive force should be avoided to compress the deflated blood vessels to affect the image quality. The hand holding the probe should find a suitable fulcrum to ensure that the blood vessel image is placed in the center of the display (14).…”
Section: Discussionmentioning
confidence: 99%
“…A similar survey done among French intensivists showed that a proportion of intensivists are still utilising blind landmark technique rather than ultrasound guidance in placing central venous lines. In this trial we tried to define the anatomical relationship between the vein and artery at the upper part of thigh [3,4,5].…”
Section: Introductionmentioning
confidence: 99%